Banyu Penguripan at Sunan Kudus’s Well: An Interplay of Spiritual Tradition and Ecological Consciousness - Mustofa, M. Lutfi; Syihabuddin, Muhammad; Siddik, Syahril (Center for Research and Development of Religious Literature and Heritage, 2025)
This study investigates the significance and function of Banyu Penguripan within the cultural tradition of the Kudus community, focusing on its intersections with spirituality, environmental ethics and local natural resource management surrounding the sacred well of Sunan Kudus. Employing a qualitative methodology, the research incorporates fieldwork that includes in-depth interviews with religious leaders, community members and well custodians, as well as participatory observation of rituals and practices associated with Banyu Penguripan. Complementary documentation was also gathered to support the analysis with relevant secondary data. Thematic analysis was conducted to identify key patterns reflecting the integration of spiritual beliefs and environmental ethics, particularly in shaping culture-based conservation models applicable to local resource governance. Findings indicate that Banyu Penguripan functions not merely as a ritual act but as a profound symbol of the interconnected relationship between humans, nature, and the divine. The tradition embodies a form of environmental ethics that fosters communal responsibility for safeguarding natural resources, especially water, as a sacred and shared heritage. This study contributes to the discourse on sustainable environmental stewardship by proposing a culturally rooted conservation framework that emphasizes spiritual values as integral to ecological balance and intergenerational sustainability.